Mechanism and Simulation of Generating Pulsed Strong Magnetic Field - 杨显俊 王帅创 邓爱东 谷卓伟 罗浩 (Chinese physics letters, 2014)
A strong magnetic field （over 1000 T） was recently experimentally produced at the Academy of Engineering Physics in China. The theoretical methods, which include a simple model and MHD code, are discussed to investigate the physical mechanism and dynamics of generating the strong magnetic field. The analysis and simulation results show that nonlinear magnetic diffusion contributes less as compared to the linear magnetic diffusion. This indicates that the compressible hydrodynamic effect and solid imploding compression may have a large influence on strong magnetic field generation.